Identification of Human Being using Periocular Biometrics with Multi-Layered Network - Kumar, Nirgish; Komal, Komal; Raghuvamshi, CS (International Journal of Computer Sciences and Engineering, 2025)
The coronavirus disease 2019 (Covid-19) pandemic has significantly reduced people`s life expectancy and conveyed fears to people around the world. These requirements raise concerns about the long-term impact of wearing face masks and social marginalisation. This highlights the need for contactless biometry to check. Eye biometrics are the best option. Biometric characteristics-based personal identification systems are generally recommended for verifying the identity of people in public locations such as ATMs, banks, school visit systems, and airport immigration clearance systems. Compare it with other networks such as Face Net, Alexnet, DeepiristNet-A, DeepiristNet-B. recognition. The error rate is 3.39 times lower than the other errors.